Microbiota alterations are related to migraine food triggers and inflammatory markers in chronic migraine patients with medication overuse headache - Doga Vuralli; Merve Ceren Akgor; Hale Gok Dagidir; Pınar Onat; Meltem Yalinay; Ugur Sezerman; Hayrunnisa Bolay (The Journal of Headache and Pain)
Abstract Objective Chronic migraine (CM) patients with medication overuse headache (MOH) were recently shown to be associated with leaky gut and inflammation. We aimed to investigate gut microbiota profiles of CM patients with MOH, and their correlations with inflammatory serum parameters, migraine food triggers, and comorbid anxiety and depression. Materials and methods The study included women participants (32 CM patients with NSAID overuse headache, and 16 healthy non-headache sufferers). Migraine duration, monthly migraine headache days, presence of irritable bowel syndrome symptoms, and HADS-D and HADS-A scores were recorded. Serum samples were collected to measure circulating LPS, HMGB1, HIF-1α, and IL-6. The gut microbiota profiles of the patients were evaluated using fecal samples. Results Serum LPS, HMGB1, HIF-1α, and IL-6 levels were significantly higher in the CM + MOH group compared to the healthy controls. HADS-A and HADS-D scores were considerably higher in the CM + MOH group compared to the healthy controls. In the microbiota analysis, alpha and beta diversities were similar between the two groups. The class Clostridia, the order Eubacteriales, and the genus Ruminococcus were less abundant in the CM + NSAID overuse headache group compared to the control group. At the genus level Desulfovibrio, Gemmiger, and Dialister and at the species level, Clostridium fessum, Blautia luti, Dorea longicatena, Eubacterium coprostanoligenes, and Gemmiger formicilis were more abundant in the CM + NSAID overuse headache group compared to the control group. Desulfovibrio, Gemmiger, Dialister, Ethanoligenens harbinense, Eubacterium coprostanoligenes, Dorea longicatena, and Thermoclostridium stercorarium showed positive correlations and Clostridia bacteria showed negative correlations with migraine food triggers. Positive correlations were found between LPS and Hapalosiphonaceae, HMGB1 and Melghirimyces, HIF1-α and Rouxeilla and Blautia luti, IL-6 and Melghirimyces and Ruminococcus. Conclusion In CM patients with MOH, we have revealed the presence of dysbiosis towards an inflammatory state, and positive correlations were shown between altered gut microbiota and inflammatory serum parameters and migraine food triggers.